The characteristics of coronary-pulmonary artery fistulas and the effectivity of trans-catheter closure: a single center experience - Liu, Xin; Zhang, Lei; Qi, Zhiyong; Fan, Mengkang; Ge, Junbo (Journal of Thoracic Disease, 2019)
Background: Due to the low prevalence, the optimal treatment strategy of coronary-pulmonary artery fistula (CPF) remains unclear, and there are no established therapeutic guidelines available. The purpose of this study is to investigate the characteristics of CPF, and evaluate the effectivity of trans-catheter closure (TCC) for CPFs. Methods: Patients with CPFs were retrospectively reviewed and enrolled according to the inclusion criteria. The data of clinical manifestations, physical signs, electrocardiogram (ECG), echocardiography, coronary CTA, coronary angiography and intervention procedure were collected. The telephone follow-up was conducted to evaluate the prognosis. Results: The most common presenting complaint was dyspnea (n=21, 48.84%), followed by chest pain (n=10, 23.36%), palpitation (n=6, 13.95%), dizziness (n=3, 6.98%), and syncope (n=3, 6.98%). Most patients were coupled with single fistula (n=17, 39.53%) or two fistulas (n=23, 53.49%). Thirty fistulas (41.67%) involved the left anterior descending (LAD) artery, 28 fistulas (38.89%) involved the right coronary, 9 fistulas (12.50%) involved the left main trunk, and 5 fistulas (6.94%) involved the circumflex branch. Most of the fistulous tracts originated within the proximal one-third of the coronary arteries, only 6 fistulous tracts (8.33%) originated from the distal segment of the coronary arteries. The size of fistulas arranged from 1 mm to 8 mm, with an average of 3.45 mm. Thirty-five patients (81.40%) with 63 fistulas (87.50%) were successfully treated by percutaneous transcatheter closure. Thirty-eight patients accepted the 6-month follow-up, 36 patients (94.74%) were asymptomatic and 2 patients (5.26%) with palpitation. In conclusion, patients with more fistulas, larger fistula diameter and more severe left-to-right shunt are always coupled with more obvious clinical manifestations. The trans-catheter coil embolization is an effective method for the closure of CPFs. Conclusions: patients with more fistulas, larger fistula diameter and more severe left-to-right shunt are always coupled with more obvious clinical manifestations. The trans-catheter coil embolization is an effective method for the closure of CPFs.